A process model linking physiological arousal and fear recognition to aggression via guilt in middle childhood. (February 2021) - Colasante, Tyler; Jambon, Marc; Gao, Xiaoqing; Malti, Tina
Abstract: Aggression coincides with emotional underarousal in childhood, but we still lack an understanding of how underarousal contributes to aggression. With an ethnically diverse sample of 8-year-olds ( N = 150), we tested whether physiological underarousal and lower fear recognition were indirectly associated with heightened aggression through dampened guilt feelings. Caregivers rated children's aggressive behavior. We assessed children's skin conductance (SC) and respiratory sinus arrhythmia (RSA) while they imagined transgressing norms and measured their fear recognition with a facial morph task. Children reported guilt or lack thereof after hypothetically transgressing. The interaction of decreasing SC and increasing RSA (i.e., physiological underarousal) and poor fear recognition were indirectly associated with higher aggression through their associations with lower guilt. Emotional underarousal may contribute to aggression by disrupting the normative development of guilt. We discuss strategies to improve social-emotional acuity and reduce aggression in children with blunted physiological arousal and fear recognition.